"KOKSARA BAKAR" – FROM VISION TO DECLINE - Bruno Raguž (Senjski Zbornik)
This paper presents the first comprehensive analysis of the business operations of the Bakar Coke Plant, examining the reasons behind its launch, the invested capital and construction investments, key performance indicators through the analysis of coke production, and the plant’s impact on the town of Bakar. In the end, the paper briefly touches on the collapse of the coke plant and its legacy in Bakar.